2015
DOI: 10.5406/jamerfolk.128.509.0273
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Voices on the Web: Folksonomies and Endangered Languages

Abstract: Examining categories created by Sami users on Twitter, this article investigates the advantages and limits of global social media for a small localized group. Folksonomies illustrate the empowering potential of Twitter as a site of performance for continuity of cultural practices, vernacular expressions, and "artistic communication in small groups" (Ben-Amos 1971).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…There is evidence of its continuing relevance in current folkloristics (see for example , Cara 2003;Cocq 2015;Mould 2005;Cashman 2011;Gravot 2015;Savoleinen 2017). The spoken word, and its written derivatives in such online venues as Twitter posts, remains at the center of social life in the world's societies.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of its continuing relevance in current folkloristics (see for example , Cara 2003;Cocq 2015;Mould 2005;Cashman 2011;Gravot 2015;Savoleinen 2017). The spoken word, and its written derivatives in such online venues as Twitter posts, remains at the center of social life in the world's societies.…”
Section: Discussionmentioning
confidence: 99%
“…Movements such as the Arab spring (cf. Howard et al 2011;Khondker 2011), citizen journalism (Allan 2009;Hayes, Singer & Ceppos 2007), indigenous struggles against colonial power (Cocq 2015;Lindgren & Cocq 2016) or patients' attitudes in relation to health institutions (Johansson 2013;Goldstein 2015) are some examples of where digital tools and social media are used to raise awareness about alternative narratives. This view has also been applied to people with disabilities, whose voices are too often marginalized in relation to the majority society (cf.…”
Section: Negotiating Power Onlinementioning
confidence: 99%
“…20 These assertions are supported by the folklorist Coppélie Cocq's observation that folksomonies created via Twitter hashtags by Sámi people indigenous to Sweden and Norway have opened 'new modes for the production of knowledge' that contribute to their 'continuity of expressive culture' and provide valuable metadata that are captured nowhere else. 21 This was also the experience of Wellen and Sieber, who found that preexisting metadata schemes could not adequately address their needs in developing an ontology dataset for cross-culturally interpreting Cree conceptualisations of hydrography in Canada, which prompted them to use Semantic Web techniques in realising this aim. 22 By contrast, the Europeana OWL ontology dataset has not been geared to interpret ideas and phenomena transculturally.…”
Section: The Medium Is the Messagementioning
confidence: 99%